EFFECT OF ONLINE BUYING EXPERIENCE ON CUSTOMER LOYALTY - Kurniawan Yunus Ariyono; Sukma Irdiana; Kusnanto Darmawan (International Journal of Social Science, 2022)
This study aims to determine and analyze how far the buying experience can affect the loyalty of Traveloka Online Experience users. This study uses the independent variable (X) namely online buying experience and the dependent variable (Y) namely customer loyalty. The population of this study is all consumers who use Traveloka Online Experiance in the city of Surabaya. Sampling was carried out using the Non Probability Sampling technique with the Purposive Sampling method. The criteria for determining the sample used in this study are as follows: Users who have used Traveloka Online Experience for more than 3 months. With a sample of 100 respondents. The data analysis method used is simple linear regression analysis. The results obtained from this study indicate that the experience of buying online greatly affects consumers' loyalty to a product or service. This is evident from the trust and satisfaction of consumers for the product or service purchased. So that consumers will indirectly introduce the product to others.